Dwarf stellar haloes: a powerful probe of small-scale galaxy formation and the nature of dark matter. Issue 3 (3rd December 2021) - Deason, Alis J; Bose, Sownak; Fattahi, Azadeh; Amorisco, Nicola C; Hellwing, Wojciech; Frenk, Carlos S
ABSTRACT: We use N -body cosmological simulations and empirical galaxy models to study the merger history of dwarf-mass galaxies (with M_halo10^10 M_ ). Our input galaxy models describe the stellar mass–halo mass relation, and the galaxy occupation fraction. The number of major and minor mergers depends on the type of dark matter; in particular, minor mergers are greatly suppressed in warm dark matter models. In addition, the number of mergers that bring in stars is strongly dependent on the galaxy occupation model. For example, minor mergers are negligible for stellar halo growth in models with a high mass threshold for galaxy formation (i.e. 10^9.3 M_ at z = 0). Moreover, this threshold for galaxy formation can also determine the relative difference (if any) between the stellar haloes of satellite and field dwarfs. Using isolated simulations of dwarf–dwarf mergers, we show that the relative frequency of major and minor mergers predict very different stellar haloes: Typically, 'intermediate' dark matter merger ratios (∼1:5) maximize the growth of distant stellar haloes. We discuss the observability of dwarf stellar haloes and find that the surface brightness of these features are incredibly faint. However, when several dwarfs are stacked together, models that form particularly rich stellar haloes could be detectable. Finally, we show that stellar streams in the Galactic halo overlapping in phase space with known dwarf satellites are likely remnants of their stripped stellar haloes. The mere existence of dwarf stellar haloes can already put constraints on some small-scale models, and thus observational probes should be a high priority.